Child alarm detector for car application / Shahrul Hisyam Shafie , Nur Atiqah Adila Adnan, Nurul Amirah Wahab & Shaiful Bakhtiar Hashim - Shafie, Shahrul Hisyam; Adnan, Nur Atiqah Adila; Wahab, Nurul Amirah; Hashim, Shaiful Bakhtiar (Faculty of Electrical Engeneering, 2015)
A child alarm detector for car application is a technology to reduce the amount of child death because of their parent’s negligence who forgot their child in the car. Besides that, it is to increase the level of safety for the passengers in the car. This project used IC ATMEGA which has been programed by Arduino coding. For this circuit, the voltage that is used is 5V. For another input, motion detectors are combined in the circuit. There is switch is used in this circuit. The switch is functioning as a motion detector. The switch is used because there is no motion detected component in the software. When the switch is on, the LED and the buzzer will be on.